1997
DOI: 10.1210/en.138.10.4435
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Dehydroepiandrosterone and EM-800 on Bone Mass, Serum Lipids, and the Development of Dimethylbenz(A)Anthracene-Induced Mammary Carcinoma in the Rat

Abstract: Although treatment with dehydroepiandrosterone (DHEA) and the antiestrogen EM-800 alone decreased dimethylbenz(A)anthracene (DMBA)-induced mammary tumor incidence from 95% to 57% and 38%, respectively, approximately 9 months after DMBA administration, only two tumors developed in the group of animals that received the combination of DHEA and EM-800, and these two tumors disappeared before the end of the experiment (P < 0.01 vs. DHEA or EM-800 alone). Average tumor number per tumor-bearing animal as well as ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…11,12 The present study extends these ®ndings by demonstrating that treatment of OVX rats with EM- HCl is at least as effective as estrogen replacement therapy in reverting obesity and its related lipid and glucoseainsulin abnormalities induced by OVX. Estrogen removal through OVX profoundly altered energy balance and lipid metabolism, as previously described by us and others 4 ± 7,19,20 In brief, OVX increased energy intake and food ef®ciency, which resulted in a larger deposition of body energy, mainly in the form of fat.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…11,12 The present study extends these ®ndings by demonstrating that treatment of OVX rats with EM- HCl is at least as effective as estrogen replacement therapy in reverting obesity and its related lipid and glucoseainsulin abnormalities induced by OVX. Estrogen removal through OVX profoundly altered energy balance and lipid metabolism, as previously described by us and others 4 ± 7,19,20 In brief, OVX increased energy intake and food ef®ciency, which resulted in a larger deposition of body energy, mainly in the form of fat.…”
Section: Discussionsupporting
confidence: 73%
“…10 Despite its pure antiestrogenic activity in the mammary gland and endometrium, EM-652.HCl can be classi®ed as a selective estrogen receptor modulator, based on some`estrogen-like' properties of EM-800, the prodrug of EM-652, such as the prevention of bone loss and the lowering of plasma cholesterol and triglycerides. 11,12 In the course of studies on the action of EM-800, the prodrug of EM-652, collateral observations have suggested that these compounds may exert effects upon metabolic pathways associated with energy balance, glucose and lipid metabolism. 11,12 These observations, which suggested that the estrogen antagonist EM-652.HCl may exert effects that mimic, rather than antagonize, those of estrogen on energy and lipid metabolism, prompted us to undertake the present study to assess in detail such actions in a rat model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that obese women are more likely to have large tumors, greater lymph node involvement, and poorer breast cancer prognosis with 30% higher risk of mortality [5]. Levels of circulating lipids and lipoproteins have also been associated with high breast cancer risk, though published results have been varying [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…SCH 57068 and its pro-drug, SCH 57050, significantly inhibit growth and prevent development of DMBAinduced mammary carcinomas in the Sprague-Dawley rat [3][4][5]. SCH 57050 also prevents bone loss and decreases serum cholesterol levels in the ovariectomized (OVX) rat [2,6].…”
Section: Introductionmentioning
confidence: 99%